2007
DOI: 10.1111/j.1365-2842.2007.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

A global perspective on changes in the burden of caries and periodontitis: implications for dentistry*

Abstract: The structure and contents of most oral health care systems and the contents of dental curricula reflect a deep-rooted tradition for attempting to cure oral diseases by refined technological means. However, better oral health conditions for the world's populations necessitate the application of up-to-date scientific knowledge to control the major oral diseases. This review points out that not only should the structure and contents of oral health care delivery systems be based on state-of-the-art knowledge abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 124 publications
1
131
1
10
Order By: Relevance
“…3 This provides motivation for dentists to volunteer in resource-poor communities to provide dental care.…”
mentioning
confidence: 99%
“…3 This provides motivation for dentists to volunteer in resource-poor communities to provide dental care.…”
mentioning
confidence: 99%
“…Van alle mondziekten veroorzaakt cariës wereldwijd verreweg de meeste last in termen van per persoon verminderde levenskwaliteit. Dat is te wijten aan de hoge prevalentie van cariës die wereldwijd merendeels onbehandeld blijft (Baelum et al, 2007). Nationale preventieprogramma's en het toelaten van hulpkrachten in de mondzorg zouden wereldwijd een aanmerkelijke verbetering kunnen bewerkstelligen.…”
Section: Sociaaleconomische Invloed Op Mondgezondheidunclassified
“…In industrialized countries, caries incidence was between16-40% among 6 year old children and 4-33% among 12-14 year old age group [9]. Several studies found that developing countries had dental infectious diseases such as dental caries as the leading cause for dental visit in children contrary to the developed countries where it was congenital diseases and oro-dental traumatic injuries [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Dental anomalies found in Kuwaiti children were missing mandibular first molar followed by mandibular second pre-molar and maxillary first molar while in Jordan maxillary hypodontia [106 patients] was prevalent than mandibular hypodontia (46 patients) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that developing countries had dental infectious diseases such as dental caries as the leading cause for dental visit in children contrary to the developed countries where it was congenital diseases and oro-dental traumatic injuries [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Dental anomalies found in Kuwaiti children were missing mandibular first molar followed by mandibular second pre-molar and maxillary first molar while in Jordan maxillary hypodontia [106 patients] was prevalent than mandibular hypodontia (46 patients) [7][8][9][10][11][12][13][14][15][16][17]. Reason for missing teeth was found to be tooth loss due to caries in contrast to congenital absence [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%